1/xy^2+1/x^2y
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
g: (x+3y)(x-3y+2)
=(x+3y)(x-3y)+2(x+3y)
=x^2-9y^2+2x+6y
h: (x+2y)(x-2y+3)
=(x+2y)(x-2y)+3(x+2y)
=x^2-4y^2+3x+6y
i: (x^2-xy+y^2)(x+y)
=x^3+x^2y-x^2y-xy^2+xy^2+y^3
=x^3+y^3
j: (x+y)(x^2-xy+y^2)=x^3+y^3
k: (5x-2y)(x^2-xy-1)
=5x*x^2-5x*xy-5x-2y*x^2+2y*xy+2y
=5x^3-5x^2y-5x-2x^2y+2xy^2+2y
=5x^3-7x^2y+2xy^2-5x+2y
l: (x^2y^2-xy+y)(x-y)
=x^3y^2-x^2y^3-x^2y^2+xy^2+xy-y^2
Thu gọn đa thức:
\(C=-\dfrac{1}{2}x^2y-2xy+\dfrac{1}{2}x^2y-xy+xy-\dfrac{1}{3}x+\dfrac{1}{2}+x-0,25\)
\(=x^2y\left(-\dfrac{1}{2}+\dfrac{1}{2}\right)+xy\left(-2-1+1\right)+x\left(-\dfrac{1}{3}+1\right)+\dfrac{1}{2}-\dfrac{1}{4}\)
\(=-2xy+\dfrac{2}{3}x+\dfrac{1}{4}\)
a)B=3x3 -2y3-6x2y2+xy
B=(3x3-6x2y2)+(xy-2y3)
B=3x2(x-2y2)+y(x-2y2)
B=(x-2y2)(3x2+y)
tại x=\(\frac{2}{3}\)và y=\(\frac{1}{2}\)ta có B=(x-2y2)(3x2+y)=(\(\frac{2}{3}\)-2*\(\frac{1}{2}\)^2 )(3*\(\frac{2}{3}\)^2+\(\frac{1}{2}\))=\(\frac{1}{6}\)*\(\frac{11}{6}\)=\(\frac{11}{36}\)
b)C= 2x+xy2-x2y-2y
C=(2x-2y)+(xy2-x2y)
C=2(x-y)-xy(x-y)
C=(2-xy)(x-y)
tại x=\(-\frac{1}{2}\)và y=\(-\frac{1}{3}\)ta có C=(2-xy)(x-y)=(2-\(-\frac{1}{2}\)*\(-\frac{1}{3}\))(\(-\frac{1}{2}\)+\(\frac{1}{3}\))=\(\frac{-11}{36}\)
bài 1: ĐKXĐ: \(x\notin\left\{2;-2\right\}\)
\(\dfrac{x}{x+2}-\dfrac{x}{x-2}\)
\(=\dfrac{x\left(x-2\right)-x\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}\)
\(=\dfrac{x^2-2x-x^2-2x}{\left(x-2\right)\left(x+2\right)}=-\dfrac{4x}{x^2-4}\)
Bài 2:
1: \(x^2y^2-8-1\)
\(=x^2y^2-9\)
\(=\left(xy-3\right)\left(xy+3\right)\)
2: \(x^3y-2x^2y+xy-xy^3\)
\(=xy\cdot x^2-xy\cdot2x+xy\cdot1-xy\cdot y^2\)
\(=xy\left(x^2-2x+1-y^2\right)\)
\(=xy\left[\left(x-1\right)^2-y^2\right]\)
\(=xy\left(x-1-y\right)\left(x-1+y\right)\)
3: \(x^3-2x^2y+xy^2\)
\(=x\cdot x^2-x\cdot2xy+x\cdot y^2\)
\(=x\left(x^2-2xy+y^2\right)=x\left(x-y\right)^2\)
4: \(x^2+2x-y^2+1\)
\(=\left(x^2+2x+1\right)-y^2\)
\(=\left(x+1\right)^2-y^2\)
\(=\left(x+1+y\right)\left(x+1-y\right)\)
5: \(x^2+2x-4y^2+1\)
\(=\left(x^2+2x+1\right)-4y^2\)
\(=\left(x+1\right)^2-4y^2\)
\(=\left(x+1-2y\right)\left(x+1+2y\right)\)
6: \(x^2-6x-y^2+9\)
\(=\left(x^2-6x+9\right)-y^2\)
\(=\left(x-3\right)^2-y^2=\left(x-3-y\right)\left(x-3+y\right)\)
a: (3x^2-4)(x+3y)
=3x^2*x+3x^2*3y-4x-4*3y
=3x^3+9x^2y-4x-12y
b: (c+3)(x^2+3x)
=c*x^2+c*3x+3x^2+9x
=cx^2+3cx+3x^2+9x
c: (xy-1)(xy+5)
=xy*xy+5xy-xy-5
=x^2y^2+4xy-5
d: (3x+5y)(2x-7y)
=3x*2x-3x*7y+5y*2x-5y*7y
=6x^2-21xy+10xy-35y^2
=6x^2-11xy-35y^2
e: -(x-1)(-x^2+2y)
=(x-1)(x^2-2y)
=x^3-2xy-x^2+2y
f: (-x^2+2y)(x^2+2y)
=(2y)^2-x^4
=4y^2-x^4
\(\frac{1}{xy^2}+\frac{1}{x^2y}\)
\(=\frac{x^2y+xy^2}{x^3y^3}\)
\(=\frac{x+y}{x^2y^2}\)